2021
DOI: 10.1111/cas.15075
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor miR‐193a‐3p enhances efficacy of BRAF/MEK inhibitors in BRAF‐mutated colorectal cancer

Abstract: Patients with BRAF‐mutated colorectal cancer (CRC) have a poor prognosis despite recent therapeutic advances such as combination therapy with BRAF, MEK, and epidermal growth factor receptor (EGFR) inhibitors. To identify microRNAs (miRNAs) that can improve the efficacy of BRAF inhibitor dabrafenib (DAB) and MEK inhibitor trametinib (TRA), we screened 240 miRNAs in BRAF‐mutated CRC cells and identified five candidate miRNAs. Overexpression of miR‐193a‐3p, one of the five screened miRNAs, in CRC cells inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Moreover, miR-143 and miR-145 have been well established to exert tumor-suppressive effects and are beneficial for the efficacy of anti-EGFR treatment in CRC, whereas miR-31-3p comes to the opposite. It has been shown that the overexpression of miR-193a-3p can promote BRAF -mutant CRC cells apoptosis by inhibiting the expression of KRAS and myeloid cell leukemia-1 (Mcl1) through MAPK signal ( 47 ). As a tumor suppressor, miR-193a-3p promotes the efficacy of BRAF inhibitor dabrafenib (DAB) and MEK inhibitor trametinib (TRA), and enhances the anti-proliferative effect of combined therapy of DAB, TRA with cetuximab in CRC ( 47 ).…”
Section: Mirnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, miR-143 and miR-145 have been well established to exert tumor-suppressive effects and are beneficial for the efficacy of anti-EGFR treatment in CRC, whereas miR-31-3p comes to the opposite. It has been shown that the overexpression of miR-193a-3p can promote BRAF -mutant CRC cells apoptosis by inhibiting the expression of KRAS and myeloid cell leukemia-1 (Mcl1) through MAPK signal ( 47 ). As a tumor suppressor, miR-193a-3p promotes the efficacy of BRAF inhibitor dabrafenib (DAB) and MEK inhibitor trametinib (TRA), and enhances the anti-proliferative effect of combined therapy of DAB, TRA with cetuximab in CRC ( 47 ).…”
Section: Mirnasmentioning
confidence: 99%
“…Synthetic miR-143 (miR-143#12) inhibits KRAS signaling pathway activation and restores the sensitivity of cetuximabresistant CRC cells by targeting the KRAS activating protein SOS1 (43). Overexpression of miR-143 or miR-145 can increase the sensitivity to cetuximab by enhancing cetuximab-mediated antibody-dependent cellular cytotoxicity (ADCC) in CRC cells (44) (47). As a tumor suppressor, miR-193a-3p promotes the efficacy of BRAF inhibitor dabrafenib (DAB) and MEK inhibitor trametinib (TRA), and enhances the antiproliferative effect of combined therapy of DAB, TRA with cetuximab in CRC (47).…”
Section: Impact Of Mirnas On Ras Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs), containing 22 to 25 nucleotides, belong to single-stranded ribonucleic acid and exert function by degrading or inhibiting the translation of other proteins to regulate gene expression [ 7 ]. Dysregulation of miRNAs were closely associated with the occurrence of various diseases, especially cancers [ 8 12 ]. In lung cancer, miRNA-569 can be used as a tumor suppressor to induce apoptosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specific BRAF inhibitors are currently available. Oncogenic BRAF mutations occur in various malignancies, including malignant melanoma (50%), thyroid cancer (30%–50%), and colorectal cancer (10%) [ 6 ]. However, only a few cases of STS with BRAF mutation have been described [ 7 ].…”
Section: Introductionmentioning
confidence: 99%